PENGARUH IT HUMAN RESOURCE, INFRASTRUCTUR RESOURCE, RELATIONSHIP RESOURCE TERHADAP KNOWLEDGE MANAGEMENT DAN KEUNGGULAN KOMPETITIF UMKM DI KAB. KOTAWARINGIN TIMUR - Prasetyaningrum, Eka; Purwanto, Agung; Minarni, Minarni (IKRA-ITH INFORMATIKA : Jurnal Komputer dan Informatika, 2019)
This study aims to determine whether there is an influence of information technology humanresources, information technology infrastructure resources, information technologyrelationship resources on knowledge management and MSME competitive advantage in EastKotawaringin Regency. This research is a field survey research. The sample used in this studyamounted to 159 people. The hypothesis was tested using Partial Least Square with WarpPls6.0 Software. The results of testing the proposed hypothesis show evidence that human resourceinformation technology has no significant effect on knowledge management, informationtechnology infrastructure resources and information technology relationship resourcessignificantly influence knowledge management.